2018
DOI: 10.1111/php.12930
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dynamic m6A RNA Methylation in Photobiology

Abstract: N -methyladenosine (m A) is the most abundant internal RNA modification among numerous post-transcriptional modifications identified in eukaryotic mRNA. m A modification of RNA is catalyzed by the "writer" m A methyltransferase enzyme complex, consisting of METTL3, METTL14, WTAP and KIAA1429. The m A modification is reversible and can be removed by "eraser" m A demethylase enzymes, namely, FTO and ALKBH5. The biological function of m A modification on RNA is carried out by RNA-binding effector proteins called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 104 publications
(223 reference statements)
0
26
0
Order By: Relevance
“…In Drosophila melanogaster S2 cells, 1120 peaks representing transcripts of 812 genes are identified, and m6A methylation near start and stop codons is significantly enriched (Lence et al, 2016). Based on these mapping data, adenosine methylation appears to be restricted to adenosines in a consensus sequence of RRACH (where R denotes G or A, and H denotes A, C or U) in most m6A peaks across species (Linder et al, 2015;Zhao et al, 2017;Robinson et al, 2018). m6A methylation is a dynamic and reversible modification, which is instigated by a methyltransferase complex of methyltransferase-like 3 (METTL3) and METTL14, and is removed by two demethylases of fat mass and obesityassociated protein (FTO) and ALKB homologue 5 (Jia et al, 2011;Zheng et al, 2013;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila melanogaster S2 cells, 1120 peaks representing transcripts of 812 genes are identified, and m6A methylation near start and stop codons is significantly enriched (Lence et al, 2016). Based on these mapping data, adenosine methylation appears to be restricted to adenosines in a consensus sequence of RRACH (where R denotes G or A, and H denotes A, C or U) in most m6A peaks across species (Linder et al, 2015;Zhao et al, 2017;Robinson et al, 2018). m6A methylation is a dynamic and reversible modification, which is instigated by a methyltransferase complex of methyltransferase-like 3 (METTL3) and METTL14, and is removed by two demethylases of fat mass and obesityassociated protein (FTO) and ALKB homologue 5 (Jia et al, 2011;Zheng et al, 2013;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila melanogaster S2 cells, 1120 peaks representing transcripts of 812 genes are identified, and m6A methylation near start and stop codons is significantly enriched (Lence et al , ). Based on these mapping data, adenosine methylation appears to be restricted to adenosines in a consensus sequence of RRACH (where R denotes G or A, and H denotes A, C or U) in most m6A peaks across species (Linder et al , ; Zhao et al , ; Robinson et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A) is considered the most common internal modification of mRNAs. m 6 A RNA methylation regulates basic cellular events, such as tissue development, DNA damage response, and sex determination, but also plays a role in tumorigenesis [ 63 , 64 , 65 , 66 ]. Methylated adenosine residues in the form of N 6 -methyladenosines (m 6 A) present in the 5′ UTR also serve as another cap-independent translation mechanism of circRNAs.…”
Section: Functions Of Circrnasmentioning
confidence: 99%
“…They have been identified and well-characterized in animals [ 19 , 22 , 23 , 24 , 25 ], whereas only recently functional orthologs have been discovered in terrestrial model plants, such as Arabidopsis and rice [ 26 ]. Although many studies now point to the importance of RNA methylation and the essential roles writers, readers, and erasers might play in plant development and stress response [ 21 , 27 , 28 , 29 , 30 , 31 ], the functionality of most of these proteins remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that epigenetic and epitranscriptomic regulations affect the expression of clock components in several organisms [ 28 , 40 , 41 ], but only few studies have been conducted on the epigenetic and post-transcriptional controls of circadian clock functions in plants [ 42 , 43 , 44 , 45 ] and almost none on the role of RNA methylation (m 6 A) in regulating clock-related genes [ 46 , 47 ]. In mammals, it has been demonstrated that a large number of transcripts encoding core clock components, as well as clock output genes, are enriched in m 6 A methylation sites [ 40 , 48 ] and that changes in their m 6 A levels can affect circadian rhythms, cellular growth, and ultimately survival [ 49 ].…”
Section: Introductionmentioning
confidence: 99%